Comprehensive risk assessment of high-temperature disasters affecting rice production in Shanghai - Gaoyue Gu; Qiang Wang; Jun Shi; Yudan Gu; Haihong Li; Ya Wang; Jianhua Dai; Jiong Shu (Ecological Indicators)
In recent years, the rice-producing areas in Shanghai have often been threatened by extremely high temperatures. Evaluating the risk of high-temperature disasters in rice in the region is necessary for developing disaster preparedness and response reduction measures for agriculture. This study established a database for evaluating the risk of high-temperature disasters in rice. Then, eight indicators were selected from hazard, vulnerability, and exposure to assess the risk of high-temperature disasters. Simultaneously, five indicators, including heat and water, were selected to evaluate the climate suitability of rice and used as one of the exposure evaluation indicators. The corresponding weights of eight indicators selected from hazard, vulnerability, and exposure were obtained through the entropy weight method and expert scoring method. The results show that: (1) the areas with high climatic suitability for rice mainly surround the central city in the shape of a trumpet, indicating that the climate in the area from the northwest side of the central city to the area in Songjiang and Minhang is suitable for rice growth; and (2) the high-risk area for high-temperature disaster for rice in the research region mainly focuses on the southwest of Shanghai, indicating that rice yields are vulnerable to high-temperature disasters in the southwest of Shanghai. The framework proposed in this study can be applied to the risk assessment of high-temperature disasters in global rice production areas, which has practical guidance significance for agriculture and provides reference for disaster prevention, reduction, and planting planning of rice.